Penyuluhan Tabungan Simpel Untuk Membangun Kesadaran Menabung Sejak Dini Pada Siswa-Siswi SDI Al-Huda Kota Kediri - Shella Dwiyanti; Ladia Ayu Sekar Sari; Yusnita Agustin; Efendi, Rofik (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The Kediri State Islamic Institute community service conducted one of the counseling activities on "Building Awareness of Saving Early on in Al-Huda SDI Students," bearing in mind the low culture of saving among students, especially saving in a bank. This activity aims to provide knowledge and understanding of how to save using SIMPEL savings, plus tips for successfully saving pocket money given by parents. Apart from that, to introduce products in Bank Jatim Syariah The activity method uses stages, namely: visits to elementary schools to convey counseling programs; gathering information about problems that exist in elementary schools; compiling problems that occur in the school environment; preparing materials, methods, and tools to be used; implementing counseling regarding saving; and making an activity report. While the delivery of counseling materials uses lectures, questions and answers, and quizzes, The results of the activities achieved were that the children were enthusiastic about participating in the activities and gave positive responses, starting to understand the benefits of saving and also how to save using SIMPEL savings.